Daclizumab HYP versus Interferon Beta-1a in Relapsing Multiple Sclerosis - Kappos, Ludwig; Wiendl, Heinz; Selmaj, Krzysztof; Arnold, Douglas L; Havrdova, Eva; Boyko, Alexey; Kaufman, Michael; Rose, John; Greenberg, Steven; Sweetser, Marianne; Riester, Katherine; O'Neill, Gilmore; et al. (The New England journal of medicine, 2015)
BACKGROUND: Daclizumab high-yield process (HYP) is a humanized monoclonal antibody that binds to CD25 (alpha subunit of the interleukin-2 receptor) and modulates interleukin-2 signaling. Abnormalities in interleukin-2 signaling have been implicated in the pathogenesis of multiple sclerosis and other autoimmune disorders. METHODS: We conducted a randomized, double-blind, active-controlled, phase 3 study involving 1841 patients with relapsing-remitting multiple sclerosis to compare daclizumab HYP, administered subcutaneously at a dose of 150 mg every 4 weeks, with interferon beta-1a, administered intramuscularly at a dose of 30 μg once weekly, for up to 144 weeks. The primary end point was the annualized relapse rate. RESULTS: The annualized relapse rate was lower with daclizumab HYP than with interferon beta-1a (0.22 vs. 0.39; 45% lower rate with daclizumab HYP; P<0.001). The number of new or newly enlarged hyperintense lesions on T2-weighted magnetic resonance imaging (MRI) over a period of 96 weeks was lower with daclizumab HYP than with interferon beta-1a (4.3 vs. 9.4; 54% lower number of lesions with daclizumab HYP; P<0.001). At week 144, the estimated incidence of disability progression confirmed at 12 weeks was 16% with daclizumab HYP and 20% with interferon beta-1a (P=0.16). Serious adverse events, excluding relapse of multiple sclerosis, were reported in 15% of the patients in the daclizumab HYP group and in 10% of those in the interferon beta-1a group. Infections were more common in the daclizumab HYP group than in the interferon beta-1a group (in 65% vs. 57% of the patients, including serious infection in 4% vs. 2%), as were cutaneous events such as rash or eczema (in 37% vs. 19%, including serious events in 2% vs. <1%) and elevations in liver aminotransferase levels that were more than 5 times the upper limit of the normal range (in 6% vs. 3%). CONCLUSIONS: Among patients with relapsing-remitting multiple sclerosis, daclizumab HYP showed efficacy superior to that of interferon beta-1a with regard to the annualized relapse rate and lesions, as assessed by means of MRI, but was not associated with a significantly lower risk of disability progression confirmed at 12 weeks. The rates of infection, rash, and abnormalities on liver-function testing were higher with daclizumab HYP than with interferon beta-1a. (Funded by Biogen and AbbVie Biotherapeutics; DECIDE ClinicalTrials.gov number, NCT01064401.).
Keywords: Humans; lidé středního věku; Adjuvants, Immunologic; interferon beta; imunoglobulin G; Disease Progression; Double-Blind Method; Interferon-beta; adjuvancia imunologická; Female; dospělí; dvojitá slepá metoda; humanizované monoklonální protilátky; daklizumab; lidé; Daclizumab; imunosupresiva; Adult; Immunosuppressive Agents; Antibodies, Monoclonal, Humanized; Multiple Sclerosis, Relapsing-Remitting; ženské pohlaví; Kaplanův-Meierův odhad; relabující-remitující roztroušená skleróza; Male; Middle Aged; progrese nemoci; Kaplan-Meier Estimate; mužské pohlaví; Immunoglobulin G; Interferon beta-1a; interferon beta 1a